ANALISIS PENDAFTARAN MEREK “MINYAK SEHAT” BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Varianto, Andy; Retnowulandari, Wahyuni (Fakultas Hukum Universitas Trisakti, 2024)
A trademark serves as a distinguishing factor for goods and/or services produced by one company from those of similar companies. However, in practice, some trademarks contain elements that may mislead the public regarding the quality, benefits, or properties of the goods, potentially violating the provisions of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This study aims to analyze the regulations related to trademarks that cannot be registered under this legal framework and evaluate the registration procedure of the